Turk Thorac J 2022
DOI: 10.5152/turkthoracj.2022.21230
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID Pulmonary Function Test Evaluation

Abstract: OBJECTIVE: Since the lung is the most affected organ by COVID-19 disease, we aimed to evaluate the pulmonary function test, presence of hypoxemia, and Post-COVID-19 Functional Status Scale in 3- to 6-month post-COVID period. MATERIAL AND METHODS: Post-COVID-19 Functional Status Scale, pulse oxygen saturation, and pulmonary function test were evaluated in 67 outpatients/inpatients after 3-6 months following COVID-19 (positive reverse transcription-polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%